2021
DOI: 10.1371/journal.pone.0253865
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of COVID-19 outbreaks using human mobility data

Abstract: Background Contact mixing plays a key role in the spread of COVID-19. Thus, mobility restrictions of varying degrees up to and including nationwide lockdowns have been implemented in over 200 countries. To appropriately target the timing, location, and severity of measures intended to encourage social distancing at a country level, it is essential to predict when and where outbreaks will occur, and how widespread they will be. Methods We analyze aggregated, anonymized health data and cell phone mobility data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Mobility data have been used extensively during the COVID-19 pandemic to better comprehend epidemic transmission between populations ( Oliver et al, 2020 , Xiong et al, 2020 ), identify transmission hotspots ( Chang et al, 2021 ), and guide policy interventions ( Lucchini et al, 2021 ). For instance, Guan et al (2021) combined mobility data and case data comprising travel histories to assess the influence of human mobility on the COVID-19 pandemic in Brazil. Beria and Lunkar (2021) used Facebook data and found that lockdowns in Italy resulted in a near-zero reduction in both local and national mobility.…”
Section: Related Workmentioning
confidence: 99%
“…Mobility data have been used extensively during the COVID-19 pandemic to better comprehend epidemic transmission between populations ( Oliver et al, 2020 , Xiong et al, 2020 ), identify transmission hotspots ( Chang et al, 2021 ), and guide policy interventions ( Lucchini et al, 2021 ). For instance, Guan et al (2021) combined mobility data and case data comprising travel histories to assess the influence of human mobility on the COVID-19 pandemic in Brazil. Beria and Lunkar (2021) used Facebook data and found that lockdowns in Italy resulted in a near-zero reduction in both local and national mobility.…”
Section: Related Workmentioning
confidence: 99%
“…Using smart devices and digital transactions is the most rapid and convenient way to collect human mobility data for forecasting the COVID-19 pandemic [27][28][29]. While the smart devices are GPS-tracked, the locations of the transaction data can be found at retail outlets, leisure facilities and other public amenities.…”
Section: The Google Datamentioning
confidence: 99%
“…Several previous studies have focused on the effects of mobility restriction policies on COVID-19 transmission rates and have largely identi ed that mobility restrictions led to reductions in COVID-19 transmission (5,9,18,19,(10)(11)(12)(13)(14)(15)(16)(17). Fewer studies, however, have assessed the impacts of population mobility from COVID-19 policies.…”
Section: Introductionmentioning
confidence: 99%